An investigation of travel vlog content in promoting Responsible Tourist Behaviour - Jamaluddin, Ameer Firdaus (2022)
The purpose of this study is to investigate the content of travel vlog in their efforts to promote the Responsible Tourist Behaviour. Nowadays, User Generated Content (UGC) have been utilised its fullest potential in promoting tourism spots, services and products. Thus this study emphasised on the contents of travel vloggers in YouTube when they post on Kuala Tahan National Park, whether they insert the Responsible Tourist Behaviour attributes in their study or not. The RTB inputs are very essentials in promoting tourists as well as their viewers in acknowledging them to preserve the nature when visiting the National Park where minimal impacts will occur if they are well prepared and well acknowledged. By initialising YouTube videos regarding on Kuala Tahan National Park, the researcher has used the 15 RTB attributes or known as the checklist in this study which have been adopt and adapt from various scholars to observe the chosen videos through three distinct elements, their words, actions and intuitions. The researcher has used Video Content Analysis (VCA) as the type of analysis which are suitable in analysing those YouTube videos to compile their useful information and data. Thus, for the methodology, the researcher has identified 91videos that are related to the Kuala Tahan National Park and been analysed throughout this study the selection of videos is also sorted by the years above 2014 and the views more than 300 viewers for the videos due to achieve the reliability of the videos. The results recorded that 15 from 91 of the videos are scored between high and very high which three of them are very high in exposing the attributes of Responsible Tourist Behaviour as their contents in the videos. The respondents are varying from local and international. Majority of the videos exhibits the RTB attributes but incompetent as leakage can be found and room of improvements are open wide for them. Recommendations and guidelines have been introduced to aids the travel vloggers in improving their contents to promote more in Responsible Tourists Behaviour.